Recuperando memórias: Vicente Mariano e o Terreiro Senhor do Bonfim Ilê - Ajamin, Oxum; Lira, Larissa Sarmento (Anais dos Simpósios da ABHR, 2016)
Recuperando memórias: Vicente Mariano e o Terreiro Senhor do Bonfim Ilê